All-solid-state, self-powered supercapacitors: State-of-the-art and future perspectives. (1st December 2022) - Sayed, Doha M.; Allam, Nageh K.
Abstract: Our response to the current ecological crisis assesses the human future. COVID-19 pandemic clearly shows how critical the energy access is for health care services. This deliberately is pushing the world to develop practical and sustainable energy systems. To this end, solid-state supercapacitors (SS-SCs) meet the requisite metrics for the power-provisioning internet-of-things (IoTs) technology. Interestingly, recent reports have shown promising functional laboratory-designed devices that encourage their wide-reaching industrial scaling. In this article, an overview of the state-of-the-art SS-SCs is demonstrated. In particular, electrolyte-based redox-active, stretchable, recoverable, high/ low temperature tolerance, electrochromic, and re-stickable SS-SCs are discussed. Moreover, the innovative approaches for alleviating/eliminating the external power supply for frequent charging SS-SCs are outlined. In this regard, integrated self-powered emerging units including piezoelectric, triboelectric, photo, thermal, batteries, and miscellaneous hybrid strategies are utterly highlighted with a brief insight into the mechanisms involved. Most importantly, the challenges and key opportunities toward the implementation of sustainable and multifunctional next-generation reliable devices are elaborated. Graphical abstract: Unlabelled Image Highlights: Solid-state supercapacitors meet the requisite for the internet-of-things technology. An overview of the state-of-the-art promising functional laboratory-designed devices Redox-active, stretchable, recoverable, temperature tolerance, and electrochromic SCs Innovative approaches for integrated self-powered emerging units Implementation of sustainable and multifunctional all-in-one next-generation devices